Open decortication vs VATS Decortication for empyema Thoracis - Fawad Ali, Muhammad Imran, Aizaz Khattak, Afnan Fayaz, Fahad Bin Riaz, Imran Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Empyema thoracis is a severe infection that leads to the accumulation of pus in the pleural space, often requiring surgical intervention when conservative treatments fail. Objective: This study aims to compare the outcomes of these two surgical approaches in terms of operative time, complications, postoperative pain, recovery, and long-term pulmonary function. Methods: This retrospective cohort study was conducted at Medical Teaching Institution Lady Reading Hospital Peshawar during January 2018 to March 2023. Data was collected from a cohort of 855 patients. Patients diagnosed with empyema thoracis, irrespective of disease stage, and who underwent one of the two surgical procedures were included in the study. Patients who did not undergo surgery, received alternative treatments such as pleural drainage or antibiotics alone, or had contraindications to surgery were excluded from the study. Results: The VATS decortication group demonstrated significantly shorter operative times (98 vs. 135 minutes), fewer complications (wound infections 5% vs. 12%, hemorrhage 3% vs. 8%), and lower postoperative pain scores (4.2 vs. 6.8 on the Visual Analog Scale). The length of hospital stay was significantly shorter in the VATS group (6.1 vs. 9.3 days). At 6 months, patients in the VATS group had better pulmonary function (FEV1 86% vs. 82%) and higher rates of pleural space resolution (90% vs. 85%). Conclusions: It is concluded that VATS decortication offers significant benefits over open decortication in patients with empyema thoracis, including reduced operative time, fewer complications, less postoperative pain, and quicker recovery. Keywords: Empyema Thoracic, Open Decortication, VATS Decortication